Implementation of Nursing Process and Its Association with Working Environment and Knowledge in Ethiopia: A Systematic Review and Meta-Analysis - Wondimeneh Shibabaw Shiferaw; Tadesse Yirga Akalu; Abate Dargie Wubetu; Yared Asmare Aynalem (Nursing Research and Practice)
Background. The nursing process is a scientific problem-solving approach, which directs nursing care and potentially improves quality of health care service. The national pooled implementation of the nursing process in Ethiopia remains unknown. Hence, this review and meta-analysis aimed to estimate the overall implementation of the nursing process and its association with the working environment and knowledge in Ethiopia. Methods. PubMed, Scopus, Cochrane Library, Google Scholar, PsycINFO, and CINAHL were searched and complemented by manual searches. The DerSimonian and Laird random effects model was applied to estimate the pooled effect size, odds ratios, and 95% confidence interval across studies. The I2 statistic was used to check heterogeneity between the studies. Sensitivity analysis was deployed to see the effect of a single study on the overall estimation. Publication bias was examined using funnel plot and Egger’s regression test statistic. Analysis was performed using STATA™ Version 14 software. Results. Seven studies comprised of 1,268 study participants were included in this meta-analysis. The estimated pooled implementation of the nursing process in Ethiopia was 42.44% (95% CI: 36.91, 47.97%). Based on subgroup analysis, methods of outcome measurement showed that the highest overall implementation of the nursing process was observed from studies conducted using self-report technique 42.95% (95% CI: 35.76, 50.15). Nurses working in stressful environment were 81% less likely to implement the nursing process (OR 0.19, 95% CI: 0.04, 0.76), and nurses having good knowledge were 8 times more likely to implement nursing process (OR 8.38, 95% CI: 2.82, 24.86). Conclusion. The overall implementation of the nursing process in Ethiopia was relatively low. Good knowledge of nurse had paramount benefits to improve implementation of the nursing process. Therefore, nurse can be educated on the imperative of knowledge in order to enhance the nursing process implementation and to improve the overall quality of healthcare services. Furthermore, policymakers and other concerned bodies should give special attention to improving the implementation of the nursing process.